Judicial Competence, Processual Abundance and Selective Judgement: An Analysis of the Construction of Judicial Role of the Supreme Court in the Brazilian’s 1998 Constitution - Daniel Barile da Silveira (Revista de Política Judiciária, Gestão e Administração da Justiça, 2016)
The purpose of this article is: a) understand how was the distribution of constitutional powers of the Supreme Court in the light of legacy brought by the 88’s Constitution; ii) identify how is the use of these skills in order to indicate predominance, successes and difficulties of your procedural management. From the theoretical understanding of its constitutional powers, contrasted in the face of extracted usual judicial practice of quantitative studies on its procedural flow, we seek to understand what were the paths that constructed the Court's competence profile in the first quarter century (1988- 2012).